Positive effects of cell-free porous PLGA implants and early loading exercise on hyaline cartilage regeneration in rabbits. (December 2015) - Chang, Nai-Jen; Lin, Chih-Chan; Shie, Ming-You; Yeh, Ming-Long; Li, Chien-Feng; Liang, Peir-In; Lee, Kuan-Wei; Shen, Pei-Hsun; Chu, Chih-Jou
Graphical abstract: Abstract: The regeneration of hyaline cartilage remains clinically challenging. Here, we evaluated the therapeutic effects of using cell-free porous poly(lactic-co-glycolic acid) (PLGA) graft implants (PGIs) along with early loading exercise to repair a full-thickness osteochondral defect. Rabbits were randomly allocated to a treadmill exercise (TRE) group or a sedentary (SED) group and were prepared as either a PGI model or an empty defect (ED) model. TRE was performed as a short-term loading exercise; SED was physical inactivity in a free cage. The knees were evaluated at 6 and 12 weeks after surgery. At the end of testing, none of the knees developed synovitis, formed osteophytes, or became infected. Macroscopically, the PGI-TRE group regenerated a smooth articular surface, with transparent new hyaline-like tissue soundly integrated with the neighboring cartilage, but the other groups remained distinct at the margins with fibrous or opaque tissues. In a micro-CT analysis, the synthesized bone volume/tissue volume (BV/TV) was significantly higher in the PGI-TRE group, which also had integrating architecture in the regeneration site. The thickness of the trabecular (subchondral) bone was improved in all groups from 6 to 12 weeks. Histologically, remarkable differences in the cartilage regeneration were visible. At week 6, compared with SED groups, the TRE groups manifested modest inflammatory cells with pro-inflammatory cytokines (i.e., TNF-α and IL-6), improved collagen alignment and higher glycosaminoglycan (GAG) content, particularly in the PGI-TRE group. At week 12, the PGI-TRE group had the best regeneration outcomes, showing the formation of hyaline-like cartilage, the development of columnar rounded chondrocytes that expressed enriched levels of collagen type II and GAG, and functionalized trabecular bone with osteocytes. In summary, the combination of implanting cell-free PLGA and performing an early loading exercise can significantly promote the full-thickness osteochondral regeneration in rabbit knee joint models. Statement of significance: Promoting effective hyaline cartilage regeneration rather than fibrocartilage scar tissue remains clinically challenging. To address the obstacle, we fabricated a spongy cell-free PLGA scaffold, and designed a reasonable exercise program to generate combined therapeutic effects. First, the implanting scaffold generates an affordable mechanical structure to bear the loading forces and bridge with the host to offer a space in the full-thickness osteochondral regeneration in rabbit knee joint. After implantation, rabbits were performed by an early treadmill exercise 15 min/day, 5 days/week for 2 weeks that directly exerts in situ endogenous growth factor and anti-inflammatory effects in the reparative site. The advanced therapeutic strategy showed that neo-hyaline cartilage formation with enriched collagen type II, higher glycosaminoglycan, integrating subchondral bone formation and modest inflammation.